1999
DOI: 10.1002/(sici)1097-4644(19990701)74:1<119::aid-jcb13>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of SET is modulated as a function of cell proliferation

Abstract: We explored a biological role of SET as it relates to cell proliferation and differentiation. Immunohistochemical staining demonstrated that the expression of SET was ubiquitous and diffuse over the whole embryo on gestational day 15. At a later stage of development, SET was expressed at relatively lower levels and localized to specific tissues and cells. On embryonic day 19, specific SET immunoreactivity was found in the epithelium of skin, respiratory tract, intestine, and retina as well as in muscle and car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…, also known as SET␣, TAF-1␤, and PHAPII, is a nuclear protein that regulates cell cycle (21), cell proliferation (22), and cell motility (23). Moreover, I 2 PP2A controls gene transcription (24) by regulating histone acetylation (25) and is possibly involved in neuronal apoptotic pathways in AD brain (26).…”
Section: Pp2amentioning
confidence: 99%
“…, also known as SET␣, TAF-1␤, and PHAPII, is a nuclear protein that regulates cell cycle (21), cell proliferation (22), and cell motility (23). Moreover, I 2 PP2A controls gene transcription (24) by regulating histone acetylation (25) and is possibly involved in neuronal apoptotic pathways in AD brain (26).…”
Section: Pp2amentioning
confidence: 99%
“…Accumulated data have shown that, through PP2A-dependant and PP2A-independent pathways, SET plays a critical role in the cell cycle regulation and contributes to the development of hematological malignancies and solid tumors, especially gynecologic cancers [13,14]. In breast cancers, SET overexpression is a frequent molecular event associated with shorter overall and disease-free survival of patients [15].…”
Section: Introductionmentioning
confidence: 99%
“…TSPY harbors a cyclin B binding domain, similar to those of SET oncogene and nucleosome assembly proteins (NAP) (Tsuchiya et al, 1995;Schnieders et al, 1996;Lau, 1999). Some members of this protein family are involved in either regulating or modulating cell cycle progression (Altman and Kellogg, 1997;Shin et al, 1999;Chai et al, 2001;Canela et al, 2003;Pandey et al, 2003). It is uncertain what effects TSPY might have when it is aberrantly expressed in cells and/or tissues incapable of entering male meiosis.…”
Section: Discussionmentioning
confidence: 99%